Extralevator versus standard abdominoperineal excision in locally advanced rectal cancer: a retrospective study with long-term follow-up - Anu Carpelan; J. Karvonen; P. Varpe; A. Rantala; A. Kaljonen; J. Grönroos; H. Huhtinen (SPRINGER, 2022)
To analyze the results of abdominoperineal excisions (APE) for locally advanced rectal cancer at our institution before and after the adoption of extralevator abdominoperineal excision (ELAPE) with a special reference to long-term survival.A retrospective cohort study conducted in a tertiary referral center. All consecutive patients operated for locally advanced (TNM classification T3-4) rectal cancer with APE in 2004-2009 were compared to patients with similar tumors operated with ELAPE in 2009-2016.Forty-two ELAPE and 27 APE patients were included. Circumferential resection margin (CRM) was less than 1 mm (R1-resection) in 10 (24%) of ELAPE patients and 11 (41%) of APE patients (p = 0.1358). Intraoperative perforation (IOP) occurred in 4 (10%) patients and 6 (22%) patients in ELAPE and APE groups, respectively (p = 0.1336). There were 3 (7%) local recurrences (LRs) in ELAPE group and 5 (19%) in APE (p = 0.2473). There were no statistical differences in adverse events, overall survival, or disease-free survival between ELAPE and APE groups.We found a non-significant tendency to lower rates of IOP and positive CRM as well as lower rate of LR in the ELAPE group. Long-term survival and adverse events did not differ between the groups. ELAPE is beneficial for the surgeon in offering better vicinity to the perineal area and better work ergonomics. These technical aspects and the clinically very important tendency to lower rate of LR support the use of ELAPE technique in spite of the lack of survival benefit.